Global well-posedness for the 3D Newton-Boussinesq equations - Lili, Wu (Armenian Journal of Mathematics, 2016)
In this paper, we prove the global well-posedness for the Newton-Boussinesq equations in $\mathbb R^3$. By fully using the Fourier localization technique, we obtain the existence and uniqueness of smooth solutions in Hilbert spaces.